Aristolochic acid I is a substrate of BCRP but not P-glycoprotein or MRP2. (22nd August 2015) - Ma, Liping; Qin, Yahong; Shen, Zhuowei; Bi, Huichang; Hu, Haiyong; Huang, Min; Zhou, Hui; Yu, Lushan; Jiang, Huidi; Zeng, Su
Abstract: Ethnopharmacological relevance: Aristolochic acid nephropathy is a severe kidney disease caused by the administration of aristolochic acid, which is widely existed in plants of the Aristolochiaceae family. Aristolochic acid I (AAI) is the main toxic component in aristolochic acid. Aim of the study: The roles of intestinal efflux drug transporters in the transport of AAI are unclear. This study investigates the interaction between AAI and main intestinal efflux transporters. Materials and Methods: Firstly, bidirectional transport of AAI in Caco-2 cell monolayers was investigated. Then, MDCK-MDR1 (gene of P-glycoprotein (P-gp)), MDCK-MRP2 and LLC-PK1-BCRP cell lines were used for further investigation. Results: In this study, we observed that the efflux ratio of AAI in Caco-2 cell monolayers was 5.8, which indicated that efflux transporters might be involved in the transport of AAI. AAI did not inhibit Rho123 efflux by P-gp and calcein efflux by MRP2, and intracellular accumulation of AAI in P-gp or MRP2 overexpressing cells was not different from their parental cells. These results indicated that AAI was not a substrate of P-gp or MRP2. In contrast, intracellular accumulation of AAI in LLC-PK1-BCRP cells was significantly lower than in their parental cells. The presence of GF120918, a BCRP inhibitor, significantly increased AAI accumulation in BCRP overexpressing cells but not in their parental cells. In addition, bidirectional transport assay of AAI in LLC-PK1-BCRP monolayers showed that the net efflux ratios of AAI were 13.8, 8.0 and 7.0 at 20, 40 and 80 µM AAI, respectively, and decreased to 3.0, 1.9 and 2.0 by the addition of 10 µM GF120918. Conclusions: These results indicated that AAI was a substrate of BCRP but not P-gp or MRP2. Graphical abstract: